Improving ASWAJA Students’ Conceptual Skill through the Jigsaw Cooperative Learning Model at MA Bahrul Ulum Tambakberas Jombang - Dion Rizki Pratama; Hilyah Ashoumi; Lintang Ramadhani (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to examine the effect of implementing the cooperative learning model, specifically the Jigsaw technique, on students’ conceptual understanding in the Aswaja subject. The background of this research stems from the need for more interactive and collaborative learning methods to address the challenges of conventional Aswaja instruction, which tends to be textual and lacks student engagement. This research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The research subjects consisted of 32 tenth-grade students at MA Bahrul Ulum Tambakberas Jombang, divided into an experimental group (Jigsaw method) and a control group (conventional lecture method). Data were collected using pretest-posttest instruments and a Jigsaw implementation questionnaire. The results of data analysis showed a significant difference in conceptual skill between students taught using the Jigsaw method and those taught with conventional methods, with a significance value of 0,025 (< 0,05) based on the independent sample t-test. Additionally, a positive relationship was found between the implementation of the Jigsaw method and students’ conceptual abil, as indicated by a Pearson correlation significance of 0,032 and a correlation coefficient of 0,554 (moderate category). It is concluded that the cooperative learning model using the Jigsaw technique is effective in enhancing students’ conceptual skill.